Knowledge, Attitudes, and Practices for the Prevention and Vector Control of Dengue in a Colombian Rural Population: A Mixed Method Study - López-Saleme Rossana MSc; Escobar-Velásquez Katty MSc; Barajas-Lizarazo Mayra MSc (SAGE Open Nursing, 2025)
Introduction Dengue fever is a viral disease of public health concern. Adequate knowledge and self-care practices are the most effective strategies for vector control. Objective To describe the knowledge, attitudes, and practices for the prevention and vector control of dengue. Methods Mixed method study. A total of 283 residents in a Colombian rural population were studied. Relative and absolute frequency measures were used for statistical analysis of study variables; emergent categories were identified for qualitative data. Results 73% were women, 60% were housewives, and 37% had completed primary education. Both knowledge and attitudes presented low percentages in relation to the characteristics of the vector. Regarding practices, 76% did not have a positive disposition toward the use of mosquito nets. Participants perceived problems related to waste management, lack of education, and the presence of mosquitoes in covered water tanks. Conclusion The inhabitants of the surveyed population demonstrated acceptable knowledge with respect to dengue control practices; however, they neglected sources of risk in their immediate environment.